Managing Quality of Learning in Islamic Schools: An Analysis of Contributing Factors for Learning Toward Quality Improvement in Private Islamic Senior High Schools in Yogyakarta - Imam Machali (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
This study examines on how significant the contribution of the critical factors of learning in Islamic schools is which is cover to leadership, teachers' competencies, infrastructures, and culture of the Islamic schools on learning quality and their impact on Private Senior High Islamic school students' satisfaction in Yogyakarta. This study implements a quantitative approach with a method of survey. The object study is Private Senior High Islamic school teachers in Yogyakarta with inclusion criteria of non-Civil Servant and has not qualified for teacher's certification. The questionnaire is implemented in the data collection and analyzed with path correlation). The results of the study show that transformational leadership model becomes a key factor in the development of Islamic schools. Mastery of four teachers' competencies-pedagogy, professional, social, and personality-through various training have become key for the learning quality of the Islamic schools. Adequate Infrastructures, Islamic values-based of Islamic schools 'culture, and focusing their orientation on quality achievement and customer satisfaction have become the deciding factor for Islamic schools' service quality. Keywords: Leadership, Teachers' Competencies, Learning Quality, Customer Satisfaction Abstrak Penelitian ini mengkaji tentang kontribusi faktor-faktor kunci pembelajaran madrasah yang meliputi kepemimpinan, kompetensi guru, sarana prasarana, dan budaya madrasah terhadap mutu pembelajaran dan dampaknya terhadap kepuasan siswa Madrasah Aliyah Swasta di Yogyakarta. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Obyek penelitian ini adalah guru dari Madrasah Aliyah Swasta di kota Yogyakarta dengan kriteria bukan PNS dan belum lulus sertifikasi. Pengumpulan data menggunakan kuesioner dan dianalisis menggunakan multipel analisis (korelasi-path analysis). Hasil penelitian menunjukkan bahwa model kepemimpinan transformasional menjadi faktor kunci dalam pengembangan madrasah. Penguasaan terhadap empat kompetensi guru-pedagogi, profesional, sosial, dan kepribadian-melalui berbagai pelatihan menjadi kunci mutu pembelajaran madrasah. Sarana dan prasarana yang memadai, budaya madrasah yang berbasis pada nilai-nilai Islami, dan fokus serta orientasi pada pencapaian mutu dan kepuasan pelanggan menjadi faktor penentu kualitas layanan madrasah. Kata Kunci: Kepemimpinan, Kompetensi Guru, Mutu Pembelajaran, Kepuasan Pelanggan